Asimilasi Budaya Jawa dan Batak di Desa Batu Tiga Belas Kecamatan Dolok Masihul Kabupaten Serdang Bedagai - Sitorus, Mawaddah; Harahap, Indra; Sari, Ismet (YASIN, 2023)
This research is entitled "Assimilation of Javanese and Batak Culture in Batu Tiga Belas Village, Dolok Masihul District, Tengah Bedagai Regency". Assimilation occurs when there are groups of people with different cultural backgrounds interacting directly intensively for a long time. The result of the assimilation process is the thinning of the boundaries between individuals to identify themselves with common interests. That is, adjusting his will with the group. The same goes for one group to another. The formulation of the problem in this study are: 1. What is meant by cultural assimilation? 2. How do people view the assimilation of Javanese and Batak cultural marriages? This study aims to determine the assimilation of Javanese and Batak culture in Batu Tiga Belas Village, Dolok Masihul District, to determine the influence of Javanese and Batak cultural assimilation in Batu Tiga Belas Village, Dolok Masihul District, to increase knowledge for students of the Study of Religions in assimilation between two different tribes. different. The research method used by researchers is an anthropological approach. The findings of this study are: first, there is a change in language, second, there is transmigration of Javanese people to the majority Batak environment because of work in Batu Tiga Belas Village, katiga, there is education outside the village then meets other cultures and adapts, causing marriage.